Leveraging the United States Epicenter to Provide Insights on COVID‐19 in Patients With Systemic Lupus Erythematosus. Issue 12 (28th October 2020) - Fernandez‐Ruiz, Ruth; Masson, Mala; Kim, Mimi Y.; Myers, Benjamin; Haberman, Rebecca H.; Castillo, Rochelle; Scher, Jose U.; Guttmann, Allison; Carlucci, Philip M.; Deonaraine, Kristina K.; Golpanian, Michael; Robins, Kimberly; et al.
Abstract : Objective: To characterize patients with systemic lupus erythematosus (SLE) affected by coronavirus disease 2019 (COVID‐19) and to analyze associations of comorbidities and medications on infection outcomes. Methods: Patients with SLE and reverse transcriptase–polymerase chain reaction–confirmed COVID‐19 were identified through an established New York University lupus cohort, query of 2 hospital systems, and referrals from rheumatologists. Data were prospectively collected via a web‐based questionnaire and review of medical records. Data on baseline characteristics were obtained for all patients with COVID‐19 to analyze risk factors for hospitalization. Data were also collected on asymptomatic patients and those with COVID‐19–like symptoms who tested negative or were not tested. Statistical analyses were limited to confirmed COVID‐19–positive patients. Results: A total of 226 SLE patients were included: 41 with confirmed COVID‐19, 19 who tested negative for COVID‐19, 42 with COVID‐19–like symptoms who did not get tested, and 124 who remained asymptomatic without testing. Of the SLE patients with confirmed COVID‐19, hospitalization was required in 24 (59%) and intensive care unit–level of care in 4, and 4 died. Hospitalized patients tended to be older, nonwhite, Hispanic, have higher body mas index (BMI), history of nephritis, and at least 1 comorbidity. An exploratory (due to limited sample size) logistic regression analysis identified race, presence of at least 1 comorbidity, and BMI as independent predictors of hospitalization. Conclusion: In general, the variables predictive of hospitalization in our SLE patients were similar to those identified in the general population. Further studies are needed to understand additional risk factors for poor COVID‐19 outcomes in patients with SLE.